Turkey : Economic Reform and Accession to the European Union - Hoekman, Bernard M.; Togan, Sübidey (Washington, DC: World Bank and Centre for Economic Policy Research, 2012)
This volume analyzes the economic challenges confronting Turkey in its quest to accede to the European Union (EU). It focuses on the extent to which Turkey is ready to join the Single Market, comply with the EU's body of economic regulations and directives, the Acquis Communautaire, and meet the Maastricht criteria for fiscal, monetary, and exchange rate policies. This book also provides an assessment of Turkey's national program to meet the accession requirements. It describes briefly what Turkey needs to achieve on the economic policy front to satisfy the conditions for accession, the progress to date, and the likely consequences of implementing the full body of EU requirements. The book is divided into four parts: 1) An analysis of the macroeconomic policies for EU accession; 2) An analysis of the effects of integration on key sectors: agriculture; manufacturing; services industries, including banking, telecommunications, transportation, and natural gas; and network industries; 3) An exploration of key economic policy challenges, including labor market regulation, foreign direct investment challenges, and the costs and benefits of meeting the EU environmental Acquis; and 4) The quantification of the impact of EU accession and consideration of the welfare effects of integration. While the focus is on the specific situation of Turkey, the subject will be of value to all researchers with an interest in the challenges of deeper integration through regional agreements.